The error made when solving for k was that the person forgot to multiply the 4 to both the k and the 6. They only multiplied the -2 by the 4.
To solve it correctly, we need to multiply both the k and the 6 by 4.
First, we have:
(4) * k/4 + 6 = -2 * 4
When we multiply, we get:
k + 6 = -8
Then, we need to get rid of the 6 on the left side of the equation. We can do this by subtracting 6 from both sides:
k + 6 - 6 = -8 - 6
This simplifies to:
k = -14
So the correct solution is k = -14.
Original equation k/4 + 6 = -2 Describe the error that was made when solving for k Solve for the correct solution show all steps and answer like a 12 year old girl
(4) * k/4 + 6 = -2 * (4)
k+6 = -8
-6 -6
k = -14
1 answer